LAW ENFORCEMENT IN THE DEVELOPMENT CRIMINAL JURISDICTION SYSTEM IN INDONESIA UPHOLDING PANCASILA AND HUMAN RIGHTS VALUES - Surya Nita (NOMOI Law Review, 2021)
Law enforcement is the basis for the implementation of the criminal justice system in Indonesia with human rights values protected in the 1945 Constitution, Act No. 8 of 1981 Criminal Procedure Law, Act No. 39 of 1999 about Human Rights, Act No. 12 of 2005 about Ratification of International Convention of Civil and Political Rights and related regulation. Development of criminal justice is not regulated by various evidentiary procedures such as wiretapping, the process of resolving criminal case outside the court, online trials, so it is necessary for discussing: 1. How is development of criminal justice in Indonesia?; 2. How are the regulations in the development of the criminal justice in Indonesia while still human rights values?. The purposes are to analyzing the development of criminal justice in Indonesia and regulation still Pancasila and human rights values. The method used is juridical normative with literature study and analysis descriptive qualitative by describing development of the criminal justice system still human rights values. The development of criminal justice are proof by wiretapping, online trials, regulation about settlement of criminal cases out of court to reduce the convicts, justice collaborators, the extistence of checks and balances mechanisms between law enforcers. The criminal procedure code has not regulate the developmen of the criminal justice. Suggestions that development of the criminal justice should be received by upholding human rights values. So that the criminal procedure drafter to accomadate development of criminal cases and Criminal Code Bill.Keywords: Law Enforcement, Criminal Justice, Human Rights.